Orbitofrontal Maturation, Somatic Markers and Early Vulnerability:: A Comprehensive Hypothesis of “Emotional Myopia” in Drug Addiction - Torrado, Marco (2015)
The “emotional myopia” hypothesis is a theoretical reflection to increase the understanding of the psychologicalvulnerability showed by many drug addicts Instead of an incorporation, a cooperation is proposed of levels of knowledge onthe determinants of the neurodevelopment, psychoanalytical and attachment perspectives and psychobiological models of drugaddictions. Environmental inputs that change brain morphology are highlighted, not only early trauma or care deprivationbut also others derived from the long-term use of drugs as the core of vulnerability. We propose that Damasio’s hypothesisof somatic markers forms part of this theoretical formulation. The low quality of early social interactions may support anincreasing emotional disengagement, a poor maturation of the social brain, an increase of alexithymic patterns and noveltyseekingbehaviours, all potential triggers for searching for pleasure in drugs.